(Re‐)join the party! The effects of direct democracy on party membership in Europe. (27th October 2015) - PETERS, YVETTE
Abstract: It has been argued that political parties are in decline. While they used to be responsible for connecting citizens to the state by translating their preferences into policies, they have increasingly become part of the state, acting as governors instead. While this perspective emphasises parties' representative function, it is less clear what their role is in a more direct democratic context. Parties may gain support due to such context, but they may also be seen increasingly redundant in a situation where citizens can co‐decide directly. Focusing on party membership, this study tests these rival expectations on a panel of 16 West European democracies over the period 1980–2008 and finds that parties tend to have higher levels of party membership in a direct democratic context. The usage of referendums, however, does not contribute to this effect.